Meningkatkan Brand Image dengan Menggunakan Website Berbasis UI/UX - Fauzi, Ahmad; Rokhim, Muh. Alfin (CV. ITTC INDONESIA, 2026)
Meet Indonesia is a provider of high-quality goalkeeper gloves that currently markets its products through social media and e-commerce. However, the owner wants to improve the brand image through a more flexible independent platform to face intense industrial competition. This research aims to design a UI/UX-based sales website using CMS Wordpress to enhance Meet Indonesia's brand image and systematically evaluate its quality. The type of research used is action research involving 15 respondents as samples (2 computer experts, 2 marketing experts, 1 owner, and 10 consumers). Data collection techniques were carried out through observation, interviews, documentation, and Likert scale questionnaires. Data analysis was performed using the WebQual Index method to measure service quality and the HEART Framework to measure user experience. The results of the analysis using WebQual showed a WebQual Index (WQI) value of 91.67%, which falls into the